Sequência didática sobre resíduos vítreos para abordar para abordar educação ambiental na educação de jovens e adultos - Barros, Elaine Ferreira Muniz de Almeida (2023)
Glass is a 100% recyclable material and can also be reused in different ways, however, only a small part of this material returns in the correct form. It constitutes solid waste and, therefore, can be used as a theme to address issues related to Environmental Education (EE). Therefore, in this work, a didactic sequence (SD) was developed, as an educational product, to discuss the consumption and disposal of glassy waste and, at the same time, address important concepts within EA, such as type of waste, laws on disposal of these materials and recycling or reuse as a possibility of using glass waste. Thus, the following question was raised in the research: What contributions can a teaching sequence on the topic of glassy waste provide in relation to the approach to Environmental Education in the school space? To address this question, the general objective was to analyze SD, through its application in the school space, in terms of promoting in students a reflection on glassy waste and learning the topics covered; in addition to its relevance to the EA approach. The methodological basis of SD was the dynamics of the 3MPs, which is aligned with the Freirean conception of education. The educational product was developed in a state school in the city of Pimenta Bueno - RO, together with a class of ten students from Youth and Adult Education in High School, afternoon shift. The teaching resources selected were texts, videos, slides and a glass reuse workshop. The research was qualitative in nature, action research type and the data collection instruments used were a diagnostic assessment questionnaire to identify the students' previous conceptions regarding solid waste, the teacher's logbook, to note how it was developing the proposed didactic intervention, and the results of the activities requested from students. The parameters previously defined for data analysis were the identification of assimilation of the worked knowledge, the students' perception in relation to this type of waste and the interaction between the participants. Observou-se, com a aplicação da SD, que ela contribuiu para que os estudantes identificassem a importância da destinação correta desse resíduo. Foi possível perceber a ampliação do conhecimento, sendo que os impactos ambientais que podem ser causados pelos vidros foi o tópico mais destacado pelos estudantes ao final da proposta. Em relação à interação entre os participantes, identificou-se o envolvimento e a participação nas atividades propostas, a qual se atribui à abordagem dialógica na qual a SD se baseou. Esse produto educacional pode ser aplicado em abordagens interdisciplinares e para outros níveis de ensino. A SD, produto educacional desenvolvido, está disponível no site do Programa de Pós-graduação em Ensino de Ciências e Matemática (PPGECM), link dos produtos educacionais, e no portal do EduCapes sob o número http://educapes.capes.gov.br/handle/capes/743440.